DISKURSUS FILOSOFIS TENTANG KETUHANAN AGAMA HINDU: BRAHMAN, DEVA, AVATARA, DAN ISTADEVATA - Juli Ariawan, I Kadek (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
This research stems from the lack of interconnectedness in the study of Hindu divine philosophy, particularly the absence of an integrative analysis of the relationship between Brahman, Deva, Avatara, and Istadevata. Furthermore, comparative studies with Western theological thought are still limited. This research aims to philosophically analyze the relationship between these four concepts within the framework of Hindu divinity and compare them with the thinking in Summa Theologiae by Thomas Aquinas and Fides Quaerens Intellectum by Anselm of Canterbury. The method used is literary study with a philosophical analytical approach to classical texts such as the Vedas, Upanishads, and Puranas. The results of the study indicate that Brahman is the absolute reality, while Deva, Avatara, and Istadevata are functional manifestations in religious practice. Comparatively, it was found that despite ontological differences, there are similarities in the efforts to rationalize the concept of divinity. This research contributes to enriching the study of the philosophy of religion and dialogue across traditions.